NUMERICAL METHOD TO OVERCOME THE FLUID FLOW SEPARATION ON PIPE BEND 90 USING GUIDE VANE - Khalees Sedeq (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research delves more profoundly into examining fluid flow within a 90° pipe bend. Computational computations are executed utilizing the Reynolds-Averaged Navier-Stokes (RANS) equations. More precisely, this investigation utilizes the K-ε turbulence model. The present study employs a grid with the most elements used, chosen for its minimal error value. The central objective of this research revolves around mitigating flow separation by integrating a guide vane to modify the fluid flow attributes within a 90° pipe bend, with a curvature ratio R_c/D=1. In this instance, the pipe has a diameter of 0.01 m. When examining the 90° pipe bend without a guide vane, it becomes evident that flow separation occurs in the inner core region, and the maximum velocity region is situated in the outer core area. In contrast, when utilizing a guide vane in the 90° pipe bend, the fluid flow is directed more uniformly among the outer and inner core regions. Additionally, there is no identifiable low-velocity region where the guide vane is employed. Consequently, a guide vane effectively alleviates flow separation in the 90° pipe bend. Additionally, this study investigates various Reynolds numbers, namely 6×10^4,7×10^4, and 8×10^4. Increasing the Reynolds number does not significantly affect the velocity profile. However, it significantly influences the separation angle (α), with higher Reynolds numbers leading to larger α values. Furthermore, increasing the Reynolds number results in an earlier reattachment point in the 90° pipe bend without a guide vane.